Reconsideration of the temporary ADI and refined exposure assessment for Sunset Yellow FCF (E 110) - EFSA Panel on Food Additives and Nutrient Sources added to food (ANS) (EFSA Journal, 2014)
The Panel on Food Additives and Nutrient Sources added to Food (ANS Panel) has previously provided a scientific opinion re-evaluating the safety of Sunset Yellow FCF (E 110) as a food additive in the EU and establishing a temporary acceptable daily intake (ADI) of 1 mg/kg bw/day (EFSA ANS Panel, 2009). Following a request by the European Commission, the ANS Panel was asked to assess newly submitted data from a study conducted as a result of the recommendations contained in the 2009 opinion. In addition, EFSA was requested to carry out the refined exposure assessment of Sunset Yellow FCF. The new information assessed comprised an evaluation of the 28-day study report, the data considered by the Joint FAO/WHO Expert Committee on Food Additives (JECFA) in its latest evaluation from 2011, and any additional toxicological information that had become available since the completion of the previous evaluation by the ANS Panel. The ANS Panel has considered that the newly submitted data from the 28-day study and the overall available toxicological database on Sunset Yellow FCF provides a basis to revise the established temporary ADI and concluded that, based on the NOAEL of 375 mg/kg bw/day from the long-term feeding study in rats and an uncertainty factor of 100, a new ADI for Sunset Yellow FCF of 4 mg/kg bw/day can be established, in agreement with the latest evaluation by JECFA. Exposure estimates for Sunset Yellow FCF based both on the currently authorised MPLs and reported use levels provided are well below the new ADI of 4 mg/kg bw/day for all population groups. Overall, the Panel concluded that, using data provided by the food industry and Member States, the reported uses and use levels of Sunset Yellow FCF (E 110) would not be of safety concern.